Chloroquine-resistant Plasmodium malariae in south Sumatra, Indonesia. - Maguire, J; Sumawinata, I; Masbar, S; Laksana, B; Prodjodipuro, P; Susanti, I; Sismadi, P; Mahmud, N; Bangs, M; Baird, J (2002)
Oral chloroquine is the treatment of choice for uncomplicated Plasmodium malariae infections worldwide. We did a prospective 28-day in-vivo assessment of the efficacy of chloroquine for treatment of P malariae on Legundi Island in Lampung Bay, Sumatra, Indonesia. Of 28 patients, one had recurrent parasitaemia on day 28, and two had persistent parasitaemia to day 8. Whole-blood chloroquine and desethylchloroquine concentrations were at ordinarily effective levels (> or = 100 microg/L) on day 8 in both cases of persistent parasitaemia. These findings suggest that clinical resistance to chloroquine by P malariae occurs in the Indonesian archipelago of southeast Asia.